Beyond Mean Scores: Sex Differences in Literacy, Numeracy, and Problem-Solving as Intraindividual Strengths Across Age Groups - Balducci, Marco; Haider, Waseem (MDPI AG, 2026)
Abstract
The underrepresentation of women in science, technology, engineering, and mathematics (STEM) fields has been a longstanding issue. Traditionally, research on sex differences in cognitive abilities has focused on mean scores, which are often trivial and do not appear to explain sex disparities in STEM participation. Recently, intraindividual strengths have been proposed as a more relevant factor; they reflect an individual’s relative advantage in one skill (e.g., literacy) compared with a set of related skills (literacy, numeracy, and problem-solving). Previous studies have primarily examined younger cohorts, and intraindividual strengths remain unexplored across the lifespan. In this study, we employed data from the second cycle of the Programme for the International Assessment of Adult Competencies (PIAAC) including 157,525 individuals from 30 countries to assess sex differences in literacy, numeracy, and problem-solving as intraindividual strengths across five age groups (16–24, 25–34, 35–44, 45–54, and 55+ years). Consistent with previous research, women outperformed men in literacy, while men outperformed women in numeracy. These patterns were observed universally across countries and age groups. In contrast, no sex differences were observed in problem-solving. Future research should move beyond mean scores to focus on intraindividual strengths, as they may be more relevant for understanding sex disparities in STEM.